Construct Validity of Perceived Behavioral Control Instrument Among Patients with Coronary Artery Disease - Nuraeni, Aan; Sulistiani, Eka; Sutini, Titin; Mirwanti, Ristina; Prawesti Priambodo, Ayu; Sugiharto, Firman (Journal of Health and Nutrition Research, 2025)
Perceived Behavioral Control (PBC) is a key construct in the Theory of Planned Behavior (TPB) that plays an important role in predicting adherence to lifestyle changes among patients with coronary artery disease (CAD). Although the role of PBC has been widely discussed in health behavior research, no instrument has been specifically developed and validated to measure PBC in patients with cardiovascular disease (CVD), particularly CAD. This study used the Rasch analysis approach to evaluate the construct validity and reliability of the Perceived Behavioral Control Scale Related to Cardiovascular Disease (PBCCVD). This was a cross-sectional study involving 92 post-hospitalization CAD patients selected through convenience sampling. The PBCCVD instrument consists of 22 items using a 4-point Likert scale, developed based on TPB theory and previous studies and validated by experts. Data analysis was conducted using Winsteps software, covering reliability, separation, fit statistics, and unidimensionality. The instrument demonstrated high reliability (Cronbach's alpha = 0.86; item reliability = 0.94; person reliability = 0.86). The item and person separation indices were 4.18 and 2.74, respectively. All items met the fit criteria. The explained variance was 34.9%, and the eigenvalue of the first contrast was 2.6054, indicating a possible additional subdimension. The PBCCVD is a reliable and reasonably valid instrument for measuring perceived behavioral control in CAD patients. Although there is an indication of another underlying dimension, the instrument can still be effectively used in both clinical and research settings.